Determinantes de la eficiencia en las cooperativas del sector financiero del segmento 2 de la región Sierra, periodo 2019-2022 - Mera García, Robinson Eduardo (2024)
The purpose of the research was to analyze the determinants of efficiency in the cooperatives of the financial sector in segment 2 of the Sierra region, to determine its influence on financial management, period 2019-2022. Its methodological development was carried out in three phases, following a descriptive and quantitative approach: the first stage involved knowing the services offered by these institutions, using a characterization matrix and a benchmark; Next, the second phase was carried out to estimate the efficiency of the cooperatives and carry out a historical and comparative analysis of the ROA and ROE indicators for each year of study, based on their financial statements; As for the third phase, the incidence of financial management was evaluated to determine the efficiency of the cooperatives, through the CAMELS method. The results establish that 91% of the cooperatives studied present regular financial efficiency. It is concluded that, in the period 2019-2022, cooperatives have presented low levels of profitability, in addition to facing difficulties in their liquidity ratios and risk sensitivity.